The following is a mathematical proof that two equals one. What's wrong with it? Click below for the answer.

$a = b$

$aa = ab$

$aa - bb = ab - bb$

$(a + b)(a - b) = b(a - b)$

$a + b = b$

$a + a = a$

$2a = a$

$2 = 1$

$aa = ab$

$aa - bb = ab - bb$

$(a + b)(a - b) = b(a - b)$

$a + b = b$

$a + a = a$

$2a = a$

$2 = 1$

## 1 comment:

CLEARLY the problem is that your opening statement b=a is unproven, but thankfully I've got that for you.

a^2-2ab+b^2 = b^2-2ba+a^2

(a-b)^2 = (b-a)^2

(a-b) = (b-a)

2a = 2b

a = b

Now since I've just proven that, given any two numbers, they are equal, it necessarily follows that 1=2.

Post a Comment